The dental phenotype in familial adenomatous polyposis: diagnostic application of a weighted scoring system for changes on dental panoramic radiographs - Thakker, N; Davies, R; Horner, K; Armstrong, J; Clancy, T; Guy, S; Harris, R; Sloan, P; Evans, G (Journal of medical genetics, 1995)
A weighted scoring system (Dental Panoramic Radiograph Score) taking into consideration the nature, extent, and site of osseous and dental changes on dental panoramic radiographs in familial adenomatous polyposis is described. The weighting takes into consideration the incidence of the anomaly in the general population. The reliability of the system was tested by application to 85 people known to be affected by clinical or mutation analysis, 30 people lacking mutation in the adenomatous polyposis gene, and 19 people shown to be at low risk (< 1%) by linkage analysis. Using the highest thresholds, a specificity of 100% and sensitivity of approximately 68% was obtained. If all positive findings were considered as significant, sensitivity was increased to approximately 82% but the specificity was reduced to approximately 88%. Significant DPRS findings were observed at a significantly higher frequency in patients aged over 20 compared to the patients aged 20 and under. Overall, approximately 68% of the affected subjects had significant changes, and approximately 18% had normal appearance on DPR, with the remainder having changes classified as minimal or equivocal.